2011
DOI: 10.1007/s00894-011-1263-5
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-induced σ-holes and hydrogen bonding

Abstract: The strong collinear polarizability of the A-H bond in A-H···B hydrogen bonds is shown to lead to an enhanced σ-hole on the donor hydrogen atom and hence to stronger hydrogen bonding. This effect helps to explain the directionality of hydrogen bonds, the well known cooperative effect in hydrogen bonding, and the occurrence of blue-shifting. The latter results when significant additional electron density is shifted into the A-H bonding region by the polarization effect. The shift in the A-H stretching frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 47 publications
5
108
0
Order By: Relevance
“…A good illustration of the importance of polarization was provided by Hennemann et al [55], who showed that the V S,max of a hydrogen in the water molecule could be increased from its ground state value of 57 kcal/mol to 75 kcal/mol just by putting a point charge of −0.4 at a distance of 1.9 Å from the hydrogen, and could be decreased to 38 kcal/mol by putting a point charge of +0.4 at the same distance. A very graphic demonstration of the role of polarization can also be had by looking at plots showing the difference between the electronic density of a complex and those of the components prior to interaction [56][57][58].…”
Section: Discussion and Summarymentioning
confidence: 98%
“…A good illustration of the importance of polarization was provided by Hennemann et al [55], who showed that the V S,max of a hydrogen in the water molecule could be increased from its ground state value of 57 kcal/mol to 75 kcal/mol just by putting a point charge of −0.4 at a distance of 1.9 Å from the hydrogen, and could be decreased to 38 kcal/mol by putting a point charge of +0.4 at the same distance. A very graphic demonstration of the role of polarization can also be had by looking at plots showing the difference between the electronic density of a complex and those of the components prior to interaction [56][57][58].…”
Section: Discussion and Summarymentioning
confidence: 98%
“…[7][8][9] for typical examples) as well as by multifarious theoretical approaches [10]: molecular orbitals analysis [11], energetic decompositions [12], conceptual DFT [13,14], Bader's atoms-in-molecules (QTAIM) theory [15][16][17][18], etc., each of them conveying complementary insight to unravel their physical nature. Among them, the σ-hole concept [19][20][21][22][23][24], forged and developed by Politzer and coworkers, has achieved a high popularity, owing to its simplicity, its versatility and its ubiquity (since it is also at work in other non-covalent bonds like pnicogen and carbon bonds), and it has clearly represented a considerable breakthrough for the understanding of these non-conventional interactions.Let us recall that the σ-hole is plainly defined as a region of positive molecular electrostatic potential (MEP) on the outer side of the halogen atom. This space region is thus prone to interact with the lone electron pair(s) carried by the partner.…”
mentioning
confidence: 98%
“…In a matter of fact, the analysis of the molecular electrostatic potential (MEP) [70,[74][75][76] delineates the preferential interaction sites upon the formation of the H 3 SiH•••XOH and H 3 SiH•••HOX complexes. Figure 4 outlines the MEP graphs of H 3 SiH and HOF monomers as well as of I and IV complexes.…”
Section: Mep Analysis Interaction Energies Charge Transfers and Chmentioning
confidence: 99%